Variabilidade genética de três espécies da família Callichthyidae da bacia do alto Rio Paraná, Brasil - Ruiz, Henrique Bueno (2012)
The genetic variability of the species Callichthys callichthys, Corydoras aeneus and Hoplosternum littorale was estimated using the technique of starch gel electrophoresis, from three populations collected in the Paraná River basin, two collected in the river Xambre-PR (Callichthys callichthys, Corydoras aeneus) and one on the Parana River (Hoplosternum littorale). Ten enzyme systems were analyzed: aspartate aminotransferase (AAT; EC 2.6.1.1), alcohol dehydrogenase (ADH, EC 1.1.1.1), glucose-6-phosphate isomerase (GPI, EC 5.3.1.9), Glycerol-3-phosphate dehydrogenase (G3PDH, EC 1.1.1.8), Isocitrate dehydrogenase (IDH, EC 1.1.1.42), L-lactate dehydrogenase (LDH, EC 1.1.1.27), malate dehydrogenase (MDH, EC 1.1.1.37), malate dehydrogenase NADP + (ME, EC 1.1.1.40), phosphoglucomutase (PGM, EC5.4.2.2) and Peroxidase (PER, EC 5.4.2.2). We identified 19 alleles H. littorale, over 18 loci, of which only one polymorphic, in C. callichthys, 18 loci were detected, with total of 25 alleles, four polymorphic, in C. aeneus 19 loci were detected, with total of 28 alleles, including four polymorphic. The average expected heterozygosity was 0.0119 in the species H. littorale, 0.0505 in C. callichthys and 0.0578 in C. aeneus, demonstrating a low heterozygosity in H. littorale. The genetic distances showed that species are genetically different, confirming the data of traditional systematic.